Role of AI Assistance In Academic Writing: A Case Study of Arabic Language Students From Prompt To Publication - Cahya Edi Setyawan; Hunainah; Nurhapsari Pradnya Paramita; Widi Astuti; Siti Rauhillah; Ahmad Taufiq (ALSINATUNA, 2025)
This research aims to explore in depth how students of the Arabic Language Education Study Program utilize artificial intelligence (AI) in the academic writing process, and how such practices reshape pedagogical, cognitive, and ethical dimensions within higher education. This research use qualitative approach with an exploratory-interpretive case study design, data were collected through semi-structured interviews, limited participant observations, and analysis of student manuscripts before and after AI-assisted revisions. The findings reveal that students employ AI across three core functions: as a catalyst for  conceptual development and structural planning, as a linguistic and cohesive revision tool, and as a facilitator of academic self-efficacy. However, significant ethical dilemmas emerge, including ambiguity in intellectual attribution, unclear boundaries of AI contribution, and the absence of institutional regulation. Patterns of AI interaction varied by institutional context: reflective at UIN Sunan Kalijaga Yogyakarta, pragmatic at Universitas Muhammadiyah Yogyakarta, and philosophical at STAI Masjid Syuhada. This research recommends the development of AI literacy and digital ethics curricula, along with clear institutional policies regarding the use of AI in academic writing. Additionally, continuous training and equitable digital access are needed to ensure that AI integration occurs fairly and reflectively.